2012
DOI: 10.1155/2012/697603
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Activity of Sclerotia ofLignosus rhinocerus(Tiger Milk Mushroom)

Abstract: Lignosus rhinocerus, the tiger milk mushroom, is one of the most important medicinal mushrooms used by the indigenous people of Southeast Asia and China. It has been used to treat breast cancer. A cold water extract (LR-CW) prepared from the sclerotia of L. rhinocerus cultivar was found to exhibit antiproliferative activity against human breast carcinoma (MCF-7) and human lung carcinoma (A549), with IC50 of 96.7 μg/mL and 466.7 μg/mL, respectively. In comparison, LR-CW did not show significant cytotoxicity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 14 publications
(21 reference statements)
3
45
1
Order By: Relevance
“…Traditionally, the sclerotium of the tiger milk mushroom is used to treat breast cancer. Lee et al . demonstrated that CWE of the cultivated strain TM02 exhibited anti‐proliferative activity against MCF‐7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the sclerotium of the tiger milk mushroom is used to treat breast cancer. Lee et al . demonstrated that CWE of the cultivated strain TM02 exhibited anti‐proliferative activity against MCF‐7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is used to treat a variety of diseases, including cancer, cough and asthma, and as a general tonic . Current scientific literature has documented a number of bioactive properties of the sclerotium of L. rhinocerus such as enhancement of immunomodulatory activity and anti‐proliferative effect against the human breast carcinoma (MCF‐7) and lung carcinoma (A549) …”
Section: Introductionmentioning
confidence: 99%
“…Current results suggest that a small amount (4-8 μg/mL) of polysaccharide extract is able to inhibit nearly 45% growth of human lung carcinoma compared to a study by Lee et al [14] that required 466.7 μg/mL of crude extract to achieve IC 50 for human lung carcinoma (A549). In addition to the suggestion by Lee et al [14] that the cytotoxic action of the LR-CW is due to the high-molecular-weight fraction, either the proteins or protein-carbohydrate complex [14]. Hence, present results suggest high-molecular-weight beta-glucan-rich polysaccharide could be the primary candidate in the inhibition of human lung carcinoma.…”
Section: Resultsmentioning
confidence: 69%
“…Previous study by Lee et al [14] reported cold water extract (LR-CW) prepared from the sclerotia of L. rhinocerus cultivar was found to exhibit antiproliferative activity against human breast carcinoma (MCF-7) and human lung carcinoma (A549), with IC 50 of 96.7 μg/mL and 466.7 μg/mL, respectively [14]. Current results suggest that a small amount (4-8 μg/mL) of polysaccharide extract is able to inhibit nearly 45% growth of human lung carcinoma compared to a study by Lee et al [14] that required 466.7 μg/mL of crude extract to achieve IC 50 for human lung carcinoma (A549).…”
Section: Resultsmentioning
confidence: 91%
“…An in vitro study on the antioxidant activity revealed that the mushroom sclerotial extracts exhibited potent antioxidant activity (Yap et al, 2013). Lee et al (2012) demonstrated that the cold water extract of L. rhinocerotis sclerotium exhibited significant anti-proliferative activity against human breast (MCF-7), and lung (A549) adenocarcinoma cells. The polysaccharides of the L. rhinocerotis sclerotium were reported to have immunomodulatory effect by activating human innate immune cells (Wong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%